2016
DOI: 10.1002/14651858.cd010526.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Dental cavity liners for Class I and Class II resin-based composite restorations

Abstract: Background Resin-based composite (RBC) is currently accepted as a viable material for the restoration of caries for posterior permanent teeth requiring surgical treatment. Despite the fact that the thermal conductivity of the RBC restorative material closely approximates that of natural tooth structure, postoperative hypersensitivity is sometimes still an issue. Dental cavity liners have historically been used to protect the pulp from the toxic effects of some dental restorative materials and to prevent the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
0
9
0
2
Order By: Relevance
“…Moreover, no association was found between the technique used to place the bulk-fill resin (incremental and bulk) and the depth of the cavity in terms of post-operative sensitivity [ 45 ]. A Cochrane review found inconsistent evidence regarding the use of linings and restoration failures, particularly regarding post-operative sensitivity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no association was found between the technique used to place the bulk-fill resin (incremental and bulk) and the depth of the cavity in terms of post-operative sensitivity [ 45 ]. A Cochrane review found inconsistent evidence regarding the use of linings and restoration failures, particularly regarding post-operative sensitivity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…No association was found between the placement technique of the bulk-fill resin composite (incremental and bulk-filling) and the cavity depth on the postoperative sensitivity [52]. A Cochrane review found inconsistent evidence regarding the use of liners and restoration failure, particularly concerning postoperative sensitivity [54].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no evidence demonstrates a difference in the longevity of restorations placed with or without dental cavity liners. 36 Therefore, with the fact that resin composite is a poor thermal conductor, it might be stated that the application of cavity a base under a resin composite restoration should be limited to cases where a pulp capping agent (Calcium hydroxide) has been applied. 37…”
Section: Bases Under Compositesmentioning
confidence: 99%